Adaptive event-triggered fuzzy tracking control of nonlinear systems with dead-zones and unmeasurable states. Issue 16 (9th December 2020) - Hu, Yu-Han; Zhao, Ling; Wu, Li-Bing; Zhao, Nan-Nan; Zhang, Yu-Jun
Abstract : In this paper, the adaptive event-triggered tracking control of uncertain nonlinear systems with dead-zone inputs is developed based on fuzzy approximation technique. Firstly, a robust fuzzy state observer is constructed to effectively estimate all the unmeasurable states. Next, an adaptive output feedback controller with parameter updated law only containing one on-line adjusted variable is designed via the backstepping scheme. Concomitantly, a novel event-triggered condition related to the upper and lower bounds of dead-zone parameters and the decreasing function of tracking errors is given to substantially alleviate the computation load of the communication process. Moreover, the desired closed-loop stability of the resulting systems can be achieved by exploiting Lyapunov function analysis. Finally, simulation results verify the effectiveness of the proposed method.